Conception of construction information storage and retrieval system of scientific and technical library of NAU - Іванкевич, О. В.; Вахнован, В. Ю. (Problems of Informatization and Control, 2008)
New technologies, inculcated in the educational process of NAU able considerably to shorten time and zatrvty students and teachers of university on a search and treatment of information. For this reason the collective of research workers of NTB NAU offered to the library readers new information storage and retrieval system, intended for satisfaction of swingeing majority of requirement in a search both traditional paper and electronic informative resources